Biofloc and food contribution to grow‐out and broodstock of Farfantepenaeus brasiliensis (Latreille, 1817) determined by stable isotopes and fatty acids. (5th February 2018) - Magaña‐Gallegos, Eden; González‐Zúñiga, Rodrigo; Arevalo, Miguel; Cuzon, Gerard; Chan‐Vivas, Elisa; López‐Aguiar, Korinthia; Noreña‐Barroso, Elsa; Pacheco, Eduardo; Valenzuela, Manuel; Maldonado, Carlos; Gaxiola, Gabriela
Abstract: The aim of this study was to use the natural dietary markers (stable isotopes and fatty acids) during grow‐out in a biofloc system and for the egg production of Farfantepenaeus brasiliensis shrimp. Egg production was compared for two broodstock origins: biofloc and a wild origin. To delineate the relative contribution to shrimp muscle and eggs, IsoSource software was used. The most important source that contributed to grow‐out shrimp was biofloc ≥250 μm. According to the principal component analysis (PCA) applied to the fatty acid profile of food sources, the first component explains 84.4% of the variability, and the most important source of fatty acids for this component was biofloc ≥250 μm. The most important fresh food sources that contributed to egg production were Artemia biomass, polychaetes and semi‐moist feed for both broodstock origins. According to a PCA analysis of the fatty acid profiles, the most important fresh foods were polychaetes and semi‐moist feed. In conclusion, both isotopic signature and fatty acid profile of the food sources can be used successfully to determine the integration of carbon in the diets of shrimp.